Psychological defence in a structure of maternal relation to an early age child with neurological pathology - Valitova, Irina E. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article considers the features of psychological defence in the structure of mother’ relation of a to an early age child with neurological pathology. The use of the method of expert evaluation allowed us to work out a procedure for identifying the number and degree of intensity of psychological defence based on the content analysis of mothers’ responses when they complete unfinished sentences about the child and their relation to him/her. The main types of defence mechanisms are identified and the content of negation, projection, displacement, rationalization and substitution is described. It was found that the intensity of psychological defences of a mother is not associated with the age of children and the severity of neurological pathology. Emotional attitude to the child, including unconditional acceptance of the child, acceptance of oneself as a parent, and emotional background of interaction, are associated with the number and intensity of psychological defences. At the same time, the mother’s sensitivity to the child and her behaviour towards him/her are not associated with psychological defences. It is proved that the intensity of psychological defences is directly related to the mothers’ self-esteem of their character and happiness, as well as to the assessment of the child’s health level, and these connections are circular. Psychological protection of a mother during early child dysontogenesis acts as a condition for her well-being, as it distorts information about the severity of the child’s disorder and contributes to a higher self-esteem.